The concept of cultural and creative industries in European academic field and policies of the EU and Great Britain - I. I. Parkhomenko (Ukrainian Cultural Studies, 2017)
Current European integration course in Ukraine requires rethinking Ukrainian scientific and policies meaning of the cultural sphere as the set of cultural industries, which produce and distribute goods or services with special cultural value, irrespective of the commercial value they may have. According to the main UN Resolutions, UNESCO Conventions and legal activity of the European Commission since 90th of XX century cultural assets are considered to be - an instrument and resource of economic, cultural and social sustainable development of states, cities and regions. New conditions require scientific methods for modelling Ukrainian cultural industries, identification of the priority industries. Besides the concept of cultural industries European scientists and governmental officials, use the concept of creative industries, especially, for the policymaking. All that show the need for clarification of these concepts in Ukrainian scientific field and policies making practice for governmental purposes. The purpose of this article is to study the meaning of the concepts of cultural and creative industries according to the European scientific discourse and policies making documents in the EU and the UK. The article shows that modern European scientists do not use the tradition of critical interpretation of the cultural industry, which was offered by representatives of the Frankfurt School in the mid-twentieth century. Scientists improve concepts to identify the sphere of culture as an economic reality, which is reflected in the specific governmental documents of the UK, the EU and UNESCO for policies making to improve sustainable development. The models of cultural and creative industries offer a logic of distinction according to the basis of the value component: the output of the creative activity has utility that is more functional for the consumers; it could be a component of the production of other industries, not only cultural industries. Cultural output has cultural value. The purpose of the creative industries is to produce goods and services for the commercial trade. Cultural industries produce cultural content, which embodies or conveys cultural expressions.
Keywords: cultural and creative industries, EU, cultural goods and services, cultural economy, cultural diversity and expressions